Correspondence regarding the article "The asbestos fibre burden in human lungs: new insights into the chrysotile debate". Issue 6 (21st December 2017) - Oliver, L. Christine; Belpoggi, Fiorella; Budnik, Lygia T.; Egilman, David; Frank, Arthur L.; Mandrioli, Daniele; Soskolne, Colin L.; Terracini, Benedetto; Welch, Laura; Baur, Xaver
The article by Feder et al . [1] states that the lung asbestos fibre burden in 23 955 patients was analysed to address fibre type and biopersistence; data from 12 patients undergoing two tissue excisions at intervals at least 4 years were considered. All asbestos types cause asbestosis (cancer): chrysotile is not biopersistent, so fibre analysis is not diagnostic http://ow.ly/BOLC30grqYg